1999
DOI: 10.1080/01140671.1999.9514098
|View full text |Cite
|
Sign up to set email alerts
|

Rind distortion of lemon caused byBotrytis cinereaPers

Abstract: The infection process by Botrytis cinerea Pers. on lemon fruits (Citrus Union (L.) Burm.), and development of rind distortion are described. Infections occur on juvenile fruitlets soon after petal fall from hyphae growing over the surface of the fruit from adjacent colonised flower debris. The hyphae form compact infection cushions at their tips. There is a collapse of epidermal cells and several layers of underlying cells in the vicinity of the infection cushion, leading to the formation of small necrotic pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…These structures are similar to the ‘infection cushions’ or ‘complex appressoria’ of the closely related fungus Sclerotinia sclerotiorum (Hegedus & Rimmer, 2005; Jurick & Rollins, 2007). The Importance of infection cushions in fungal penetration has not yet been molecularly investigated in B. cinerea , but they were observed on different organs and plants (Sharman & Heale, 1977; Garcia‐Arenal & Sagasta, 1980; Backhouse & Willetts, 1987; Fullerton et al , 1999).…”
Section: Main Characteristics Of the Infection Processmentioning
confidence: 99%
“…These structures are similar to the ‘infection cushions’ or ‘complex appressoria’ of the closely related fungus Sclerotinia sclerotiorum (Hegedus & Rimmer, 2005; Jurick & Rollins, 2007). The Importance of infection cushions in fungal penetration has not yet been molecularly investigated in B. cinerea , but they were observed on different organs and plants (Sharman & Heale, 1977; Garcia‐Arenal & Sagasta, 1980; Backhouse & Willetts, 1987; Fullerton et al , 1999).…”
Section: Main Characteristics Of the Infection Processmentioning
confidence: 99%
“…Botrytis cinerea has long been associated with the premature flower fall of lemon, as well as destructive preharvest and postharvest fruit rot. Rind distortions were also found in association with this pathogen (Fullerton et al. 1999).…”
mentioning
confidence: 94%
“…The B. cinerea IC are multicellular appressoria that develop in planta between 24 and 48 h after spore germination. Histological studies have revealed IC from B. cinerea on a wide variety of infected plant hosts and organs: carrot roots (Sharman and Heale, 1977); bean or mung bean hypocotyls (Garcia-Arenal and Sagasta, 1980;Backhouse and Willetts, 1987), bean, cucumber or oilseed rape leaves (Akutsu et al, 1981;Van den Heuvel and Waterreus, 1983;Zhang et al, 2010), stone fruit or waxflower flowers (Fourie and Holz, 1994;Dinh et al, 2011), lemon or persimmon fruits (Fullerton et al, 1999;Rheinländer et al, 2013) and onion epidermis (Choquer et al, 2007). Lastly, B. cinerea IC also develop in vitro, in culture over hard surfaces (Backhouse and Willetts, 1987).…”
Section: Introductionmentioning
confidence: 99%